“To Treat or Not To Treat?”: An Exploratory Study of Medical Practitioners' Perspective on Clinical Ethics in Stem Cell Therapies - Shariat, Sadaf (2011)
This study investigates the practitioners‘ perception toward an ethical Stem Cell therapy. Reviewing literature, it is revealed that studies on Stem Cell therapies are predominately focus on ethical aspects of Stem Cell researches, commercialization, and concept of ethic support in clinical practice; whereas the notion of clinical ethics in Stem Cell therapies and particularly medical practitioners‘ perspective is noticeably absent from contemporary clinical ethics and Stem Cell therapy discussions. In order to evaluate the recognition of clinical research values and ethical dilemmas among practitioners, a synthesized model of Clinical Research Ethics (Emanuel et al, 2000) is utilized in this study. Subsequently, the research employs a synthesize Model of Ethical decision making (Ferrell et al, 1989) to establish a better understanding of factors which may affect decision making process in practitioners. This research adapts a qualitative approach and develops by using two major vehicles of a critical research; a vigorous study of literature in the process of secondary data collection which is linked to empirical finding of this research. In depth semi structured interviews are conducted to assist author in evaluation of perception of medical practitioners who are involved with these ethical issues daily. The secondary data is extracted from numerous books, academic journals, and relevant cases of Stem Cell scandals, guidelines, international declaration, and so many others.The study includes three major findings. First, a thorough junction is revealed between literature and perception of medical practitioners. Ethical requirements of clinical researches (Emanuel model of clinical research ethics) including Stem Cell therapies are approached with ethical awareness. However, only concepts of informed consent and independent review are approached differently among samples from different countries. Secondly, there appear to be a type of unanimous reluctance among practitioners in offering Stem Cell therapies regardless of their nationality and speciality. And lastly, such reluctance is embedded in diverse justification and a variety of situational factors have influenced practitioners‘ intention to make an ethical decision making. This fact is consistent with the adapted model (Ferrell et al, 1989) in this research. Present research is expected to contribute to knowledge by providing in depth understanding of Stem Cell clinical ethics and willingness of practitioners by discovering the reality of practice from medical practitioners‘ perspective. There appears a call for further cross cultural studies in order to provide practical implication to the Stem Cell business particularly in countries with limited experience of providing ethic support in clinics.